A phase I, first‐in‐human, randomized dose‐escalation study of anti‐activated factor XII monoclonal antibody garadacimab. Issue 3 (3rd December 2021) - McKenzie, Andrew; Roberts, Anthony; Malandkar, Sourabh; Feuersenger, Henrike; Panousis, Con; Pawaskar, Dipti
Abstract: Factor XII (FXII) is the principal initiator of the plasma contact system and has proinflammatory and prothrombotic activities. This single‐center, first‐in‐human phase I study aimed to assess the safety and tolerability of single escalating doses of garadacimab, a monoclonal antibody that specifically inhibits activated FXII (FXIIa), in healthy male volunteers. Volunteers were randomized to eight cohorts, with intravenous (i.v.) doses of 0.1, 0.3, 1, 3, and 10 mg/kg and subcutaneous (s.c.) doses of 1, 3, and 10 mg/kg. Six volunteers in each cohort received garadacimab or placebo in a ratio of 2:1. Follow‐up for safety lasted 85 days after dosing. Blood samples were collected throughout for pharmacokinetic/pharmacodynamic analysis. Forty‐eight volunteers were enrolled: 32 received garadacimab and 16 received placebo. Most volunteers experienced at least one treatment‐emergent adverse event (TEAE), predominantly grade 1. No serious TEAEs, deaths, or TEAEs leading to discontinuation were reported. No volunteers tested positive for garadacimab antidrug antibodies. Garadacimab plasma concentrations increased in a dose‐dependent manner. Sustained inhibition of FXIIa‐mediated kallikrein activity beyond day 28 resulted from 3 and 10 mg/kg garadacimab (i.v. and s.c.). A dose‐dependent increase in activated partial thromboplastin time with no change in prothrombin time was demonstrated. Garadacimab (single‐dose i.v. and s.c.) was well‐tolerated in healthy volunteers. Dose‐dependent increases in plasma concentration and pharmacodynamic effects in relevant kinin and coagulation pathways were observed. These results support the clinical development of garadacimab, including in phase II studies in hereditary angioedema and coronavirus disease 2019 (COVID‐19).